Adequacy of Anesthesia Guidance for Combined General/Epidural Anesthesia in Patients Undergoing Open Abdominal Infrarenal Aortic Aneurysm Repair; Preliminary Report on Hemodynamic Stability and Pain Perception - Michał Jan Stasiowski; Seweryn Król; Paweł Wodecki; Nikola Zmarzły; Beniamin Oskar Grabarek (MDPI AG, 2024)
Background/Objectives: Hemodynamic instability and inappropriate postoperative pain perception (IPPP) with their consequences constitute an anesthesiological challenge in patients undergoing primary elective open lumbar infrarenal aortic aneurysm repair (OLIAAR) under general anesthesia (GA), as suboptimal administration of intravenous rescue opioid analgesics (IROAs), whose titration is optimized by Adequacy of Anaesthesia (AoA) guidance, constitutes a risk of adverse events. Intravenous or thoracic epidural anesthesia (TEA) techniques of preventive analgesia have been added to GA to minimize these adverse events. Methods: Seventy-five patients undergoing OLIAAR were randomly assigned to receive TEA with 0.2% ropivacaine (RPV) with fentanyl (FNT) 2.5 μg/mL (RPV group) or 0.2% bupivacaine (BPV) with FNT 2.5 μg/mL (BPV group) or intravenous metamizole/tramadol (MT group). IROA using FNT during GA was administered under AoA guidance. Systemic morphine was administered as a rescue agent in all groups postoperatively in the case of IPPP, assessed using the Numeric Pain Rating Score > 3. The maximum score at admission and the minimum at discharge from the postoperative care unit to the Department of Vascular Surgery, perioperative hemodynamic stability, and demand for rescue opioid analgesia were analyzed. Results: Ultimately, 57 patients were analyzed. In 49% of patients undergoing OLIAAR, preventive analgesia did not prevent the incidence of IPPP, which was not statistically significant between groups. No case of acute postoperative pain perception was noted in the RPV group, but at the cost of statistically significant minimum mean arterial pressure values, reflecting hemodynamic instability, with clinical significance < 65mmHg. Demand for postoperative morphine was not statistically significantly different between groups, contrary to significantly lower doses of IROA using FNT in patients receiving TEA. Conclusions: AoA guidance for IROA administration with FNT blunted the preventive analgesia effect of TEA compared with intravenous MT that ensured proper perioperative hemodynamic stability along with adequate postoperative pain control with acceptable demand for postoperative morphine.